Membranous Glomerulonephritis as an Uncommon Presentation of Secondary Syphilis: A Reminder on Therapeutic Decision-Making in Clinical Practice - Faisal Inayat MBBS; Talal Almas BS; Syed Rizwan A. Bokhari MD; Aun Muhammad MBBS; Moh'd A. Sharshir MD (SAGE Publishing, 2020)
Membranous glomerulonephritis is one of the common causes of nephrotic syndrome in the adult population. It is idiopathic in the majority of patients, but the secondary forms can be seen in the setting of autoimmune disease, cancer, infection, and following exposure to certain medications. However, subclinical syphilis-related membranous nephropathy remains a particularly rare clinicopathologic entity in modern times. In this article, we chronicle an interesting case of latent syphilis masquerading as membranous glomerulonephritis, which resolved with benzathine penicillin without requiring immunosuppressive treatment. We further supplement this paper with a concise review of the relevant literature that delineates the utility of appropriate antibiotic therapy in the management of luetic membranous nephropathy. Clinicians should remain cognizant of secondary syphilis while evaluating patients for possible glomerulonephritis or those presenting with proteinuria. Additionally, patients with hepatitis B, hepatitis C, and human immunodeficiency virus infections are not infrequently coinfected with Treponema pallidum . Therefore, a high index of suspicion for systemic manifestations of syphilis such as nephrotic syndrome is warranted in the setting of a coinfection. Prompt diagnosis and treatment of syphilis may result in resolution of proteinuria, without the need for standard immunosuppressive therapy commonly used in clinical practice.